Druggable molecular alterations in bile duct cancer: potential and current therapeutic applications in clinical trials. (2nd September 2021) - Bourien, Héloïse; Lamarca, Angela; McNamara, Mairéad G; Hubner, Richard A; Valle, Juan W; Edeline, Julien
ABSTRACT: Introduction : Cholangiocarcinomas (CCA) are rare tumors that are associated with a variety of molecular alterations. Many of these alterations are now actionable using drugs currently in development, and CCA may be a perfect example of application of a precision oncology approach. However, development of drugs in CCA faces the challenge of targeting rare alterations in a rare disease. Areas covered : In this review, we present the current data on targeted therapies in development for CCA, focusing on IDH1, FGFR2, BRAF, and HER2 alterations. We also discuss rationale for targeting other alterations, currently without specific development in CCA. We searched PubMed and google scholar in February 2021 for relevant articles and presentation in recent congress regarding the literature on molecular alterations, drugs in cholangiocarcinomas and biliary tract cancers. Expert opinion : Despite a strong rationale and promising early results, applying a precision oncology approach in CCA for everyday patients is still exposed to significant challenges: obtaining the molecular portrait of these tumors due to difficulties with biopsy access, complexities of drug development in subgroups of these relatively rare tumors, and sub-optimal access to drugs outside clinical trials.